Penatalaksanaan Fisioterapi Pada Penyakit Paru Obstruksi Kronik Di Rskp Respira Yogyakarta - Hasanah, Dyah Uswatun; , Isnaini Herawati, S. Fis, M.Sc (2016)
Background; Chronic Obstructive Pulmonary Disease (COPD) is a permanent blockage of the respiratory tract caused by emphysema and chronic bronchitis. According to the American College of Chest Physicians / American Society, (2015) "COPD is defined as a group of lung diseases characterized by slowing the flow of air that is settled" (Irianto, 2014). Objective; Knowing the benefits of Nebulizer, Chest of therapy, and the mobilization of the thoracic cage to reduce breathlessness, sputum issued, and increase thoracic Expansion was driven in patients with COPD Results; After treatment for 6 times, showed the degree of breathlessness T1: 5 to T4: 2, margin expansion cage thorax from the axilla in T1: 2 cm into T4: 3 cm, of intercostalis IV on T1: 3 cm into T4: 3, 5 cm, of procesus xypoideus at T1: 2 cm into T4: 3.5 cm. T1 layout results sputum: sputum is located in the upper lobes of the right lung and the left anterior portion and the lower lobe of the right lung and the posterior part of the T4: sputum layout is still the same as in T1 but the sound produced Ronchi diminishing and virtually disappeared Conclusion; Award Nebulizer, Chest therapy and mobilization of the thoracic cage can reduce breathlessness, increase the expansion of the thoracic cage, and reducing sputum in COPD patients. Keyword; COPD, Nebulizer, Chest therapy, and the mobilization of the thoracic cage